Advertising of unhealthy foods and beverages around primary and junior high schools in Ghana’s most urbanized and populous region - Amevinya, G.S.; Aryeetey, R.; Vandevijvere, S.; et al. (Frontiers in Public Health, 2022)
Introduction: The advertising of energy-dense, nutrient-poor foods and beverages is a common feature in obesogenic food environments. Such advertising, within and around settings where children live, learn, and play, negatively and miscellaneous (including soup cubes, seasonings, and tea) products. About 4% of food advertisements had only a product/brand name or logo displayed. One out of two of the foods and beverages advertised were ultra-processed foods, 30% processed, 3% processed culinary ingredients, and 17% unprocessed or minimally processed foods. Sugar-sweetened beverages were the most advertised food product type (32%). Promotional characters were found on 14% of all food advertisements (most–69% were cartoons or manufacturer’s characters), while 8% of all food advertisements had premium offers o
Research Article
Keywords: food environments; food advertising; unhealthy foods; schools; children; Ghana